Äquivalenzwerte im biologischen Material - Beurteilung bei Exposition gegenüber kanzerogenen Arbeitsstoffen - Drexler, Hans (Zentralblatt für Arbeitsmedizin, Arbeitsschutz und Ergonomie, 2016)
Biological monitoring has been used for many years in workers exposed to carcinogenic substances at the workplace, even though threshold values cannot be evaluated. As a rule, no concentrations can be given for carcinogenic substances where below these limits a danger to health no longer exists; however, for many carcinogenic substances used at the workplace relationships between the external (ambient in air) and internal (biological material) exposure can be derived (exposure equivalents for carcinogenic substances). In this way it can be recognized whether the internal concentrations correspond to the external concentrations or whether an additional exposure (e.g. skin resorption) exists. In Germany a classification into tolerable and acceptable risk-related levels for certain concentrations in air is applied for occupational exposure to carcinogenic hazardous substances at the workplace. These ambient concentrations are assigned to 910 equivalence values in biological material in the technical regulations for hazardous substances (TRGS), by which it can be seen whether the exposure of individual workers lies within the acceptable or still tolerable ranges of these risks. If these risks have not been described or data are lacking to describe the relationship between external and internal exposure, the biological reference values for hazardous workplace substances can be consulted for the assessment. A clear exceedance of the reference value threshold indicates an additional exposure with the accompanying health risks, without being quantifiable. Under these circumstances measures for workplace hygiene should be initiated.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Biomonitoring; Carcinogens; Primary prevention; Reference values; Risk assessment